Concentration‐ and flux‐based dose–responses of isoprene emission from poplar leaves and plants exposed to an ozone concentration gradient. (14th July 2017) - Yuan, Xiangyang; Feng, Zhaozhong; Liu, Shuo; Shang, Bo; Li, Pin; Xu, Yansen; Paoletti, Elena
Abstract: Concentration‐ and flux‐based O3 dose–responses of isoprene emission from single leaves and whole plants were developed. Two poplar clones differing in O3 sensitivity were exposed to five O3 levels in open‐top chambers for 97 d: charcoal‐filtered ambient air (CF), non‐filtered ambient air (NF) and NF plus 20 ppb (NF + 20), 40 ppb (NF + 40) and 60 ppb (NF + 60). At both leaf and plant level, isoprene emission was significantly decreased by NF + 40 and NF + 60 for both clones. Although intra‐specific variability was found when the emissions were up‐scaled to the whole plant, both leaf‐ and plant‐level emissions decreased linearly with increasing concentration‐based (AOT40, cumulative exposure to hourly O3 concentrations >40 ppb) and flux‐based indices (PODY, cumulative stomatal uptake of O3 > Y nmol O3 m −2 PLA s −1 ). AOT40‐ and POD7 ‐based dose–responses performed equally well. The two clones responded differently to AOT40 and similarly to PODY (with a slightly higher R 2 for POD7 ) when the emission was expressed as change relative to clean air. We thus recommend POD7 as a large‐scale risk assessment metric to estimate isoprene emission responses to O3 in poplar. Abstract : Poplar plantations are promoted as renewable energy source but are strong isoprene emitter, which affects atmospheric chemistry and finally climate change. Here, we found both concentration‐based AOT40 and flux‐based PODY performed well and were highly negatively correlated with the isoprene emission at leaf level. When the responses were up‐scaled to the plant level, however, the O3 dose–response relationship depended on the O3 sensitivity of the clone, leaf level isoprene emission and leaf area. Results are relevant for modelling isoprene emission of plants at a regional or global scale, especially under the present and future elevated O3 conditions.